Configuring Exchange server 2000 - Mason, Liz. (Rockland, MA : Syngress, 2001)
E-mail configuration for the System Administrator. Windows 2000 users will find Configuring Exchange Server 2000 valuable for its coverage of all the popular e-mail clients, such as Outlook and Outlook Express. In addition, System and E-Mail Administrators will find the coverage of large system E-Mail Providers such as Exchange indispensable. Configuring Exchange Server 2000 focuses on e-mail configuration from the standpoint of the system administrator. It covers installation and management of all the major email programs, as well as covering mobile email, web-based email, email security and implementation of email within multinational companies. * Covers the full range of e-mail security features * Avoids theory and deals in specific safeguards and solutions that are readily available to users.
What's New in Exchange 2000 -- Active Directory Integration with Exchange 2000 -- Security Applications that Enhance Exchange 2000 -- Basic Administration -- Client Access to Exchange 2000 for E-Mail -- Deploying Exchange 2000 Server -- Defending Exchange 2000 from Attack -- Real-Time Communication in Exchange 2000 -- Application Service Providers -- Is Your Backup and Restore Really Working? -- Clustering Your Exchange 2000 Server.
Includes index.
Keywords: Microsoft Exchange server; Client/server computing; Electronic books